2014
DOI: 10.1007/s12663-014-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Costochondral Graft as Interpositional material for TMJ Ankylosis in Children: A Clinical Study

Abstract: This study indicates that using costochondral grafts to reconstruct TMJ ankylosis in children provides a good result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…27 In the present study, acceptable results were found in 8 out of 10 cases using metatarsal bone grafts for the reconstruction of the joint after resection of the ankylosed joint, with adequate mouth opening of 35.6mm. These findings are consistent with those of Sharma et al 21 In their study, satisfactory results were achieved in 8 out of 10 cases, with sufficient mouth opening of 35mm in 8 subjects. However, the findings of the current study (35.6mm) were lower than reported by Landa et al 28 who showed that the post-operative interincisal aperture was 48.5mm.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…27 In the present study, acceptable results were found in 8 out of 10 cases using metatarsal bone grafts for the reconstruction of the joint after resection of the ankylosed joint, with adequate mouth opening of 35.6mm. These findings are consistent with those of Sharma et al 21 In their study, satisfactory results were achieved in 8 out of 10 cases, with sufficient mouth opening of 35mm in 8 subjects. However, the findings of the current study (35.6mm) were lower than reported by Landa et al 28 who showed that the post-operative interincisal aperture was 48.5mm.…”
supporting
confidence: 92%
“…This is particularly true of young children who are completely unable to open their mouth. 21 The treatment of TMJ ankylosis should start as soon as the condition is recognized to minimize the restriction of facial growth. 21,22 There are three basic surgical objectives in the treatment of TMJ ankylosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations